AI-Powered Alerts for Patients and Providers to Detect Potential Health Risks - Vipin Gupta (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Artificial Intelligence (AI) has emerged as a transformative tool in healthcare, offering the ability to analyze large volumes of data and provide actionable insights. One critical application is in the early detection of potential health risks, enabling timely interventions that could save lives. This paper explores how AI-driven systems can monitor patient health data in real-time and trigger alerts to notify both patients and healthcare providers of anomalies, risks, or deteriorating conditions. By leveraging machine learning algorithms, predictive analytics, and wearable technologies, these systems enhance personalized care, reduce the burden on healthcare professionals, and improve patient outcomes. Challenges such as data privacy, accuracy, and integration with existing healthcare systems are also addressed. This study highlights the potential of AI to revolutionize health monitoring and risk management, making healthcare more proactive and responsive.
Keywords: Artificial Intelligence; Health Monitoring; Predictive Analytics; Wearable Technology; Patient Alerts; Healthcare Providers; Early Detection; Data Privacy; Personalized Medicine; Risk Management